Methanation catalyst suitable for high-concentration carbon dioxide as well as preparation method and application of methanation catalyst

Catalysts are prepared by using Al2O3-ZrO2 composite support and nitrogen-doped mesoporous carbon and other materials, and setting up a multi-layer catalyst structure in the reactor, the problems of catalyst sintering and stability are solved, and efficient methanation reaction and safe operation are achieved. .

CN119281365AActive Publication Date: 2025-01-10中煤陕西能源化工集团有限公司 +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411460655.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing methanation catalysts are prone to sintering in high-temperature reactions, have poor hydrothermal stability, resulting in short catalyst life and low device operation safety, and insufficient catalytic activity in multi-stage methanation reactions, affecting the reaction efficiency.

Method used

Using a composite support with Al2O3 and ZrO2, nitrogen-doped mesoporous carbon and silicon carbide are added as support modifiers, and CeO2, MnO2 and MgO as additives, the catalyst is prepared by ultrasonic stirring and hydrothermal aging, and in the reactor Multi-layer catalyst active layer and inert filler layer are provided to control the bed temperature and avoid local high temperatures.

Benefits of technology

It improves the heat resistance and hydrothermal stability of the catalyst, extends the service life of the catalyst and reactor, achieves ease of heating in the bed, reduces equipment investment and operation costs, and improves the efficiency and safety of the methanation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a methanation catalyst suitable for high-concentration carbon dioxide, which comprises the following components in percentage by mass: 12-85% of carrier, 1-75 wt% of carrier modifier, 10-50 wt% of active component NiO and 1-5 wt% of assistant, and the sum of the mass percentages of the components is 100%. The invention also provides a preparation method and application of the methanation catalyst suitable for high-concentration carbon dioxide. The invention provides a method suitable for methanation of high-concentration carbon dioxide, and provides a series of carbon dioxide methanation catalysts and a catalyst filling method which is simple in structure, high in reaction efficiency, mild in bed temperature rise, low in hot-spot temperature and capable of avoiding generation of a local high-temperature area. Therefore, the problems of sintering inactivation of the catalyst, low hydrothermal stability, short service life of the catalyst, poor operation safety of the device and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization of chemical tail gas, relates to a methanation catalyst suitable for high-concentration carbon dioxide, and also relates to a preparation method and application of the methanation catalyst suitable for high-concentration carbon dioxide. Background Art With the increasing depletion of non-renewable energy and the rising concentration of greenhouse gases in the atmosphere, the conversion of carbon dioxide into high-value-added chemical products has become a hot topic of research at home and abroad. Among them, the use of carbon dioxide hydrogenation to synthesize methane can not only reduce the concentration of carbon dioxide in the atmosphere, but also the methane produced can be used as fuel, which can alleviate the energy problem to a certain extent. Therefore, the development of an efficient carbon dioxide methanation technology has great practical significance. The reaction formula is: CO2(g)+4H2(g)→CH4(g)+2H2O(g) △Hθ 298K=-165kJ / mol, △Gθ 298K=-113kJ / mol Most common methanation catalysts use transition metals such as nickel, ruthenium, rhodium, and palladium as active components and are loaded on oxide carriers such as alumina, zirconium oxide, and silicon oxide. Among them, catalysts made from precious metals such as ruthenium, rhodium, and palladium have strong catalytic activity, but are expensive and cannot be used on a large scale in industrial preparation processes. In contrast, catalysts with nickel as the active phase have better application prospects. Ni / Al2O3 is the most commonly used catalyst in carbon dioxide methanation, with the advantages of good activity and low price. However, since carbon dioxide methanation produces water, nickel-based catalysts are easy to sinter during the reaction process, and are prone to carbon deposits under high-temperature reactions. They have poor water-resistant thermal stability and cannot work stably for a long time. In addition, the low-temperature reaction activity is poor, resulting in high energy consumption.

[0002] In addition, methanation is a highly exothermic reaction, and the thermal conductivity of the catalyst will affect the heat transfer efficiency of the entire system. Especially when using a heat transfer reactor, in addition to considering the reaction process, the structural design and material selection of the catalyst itself have a greater impact on the heat transfer efficiency of the system. In order to reduce equipment investment, heat transfer reactors generally use an operating temperature lower than that of adiabatic reactors. Therefore, it is of great significance to develop low-temperature and high-activity methanation catalysts.

[0003] At the same time, in a multi-stage or multi-stage methanation process, as the methanation reaction continues, in the last 1-2 stages of the methanation reaction, the CH4 and CO2 content as products in the reaction system is already very high, which will inhibit the methanation reaction to a certain extent. At the same time, side reactions such as reverse water vapor shift reaction will occur, thereby limiting the further conversion of H2 and CO into CH4 and CO2. At this time, the catalyst used in the above-mentioned last 1-2 stages of the methanation reaction is required to have high methanation reaction catalytic activity, low reverse water vapor shift reaction activity and high catalytic activity stability. However, most existing methanation reaction catalysts do not meet the above requirements.

[0004] From a thermodynamic point of view, lowering the methanation operating temperature is conducive to the forward reaction equilibrium. Theoretical calculations show that when the inlet CO+CO2 content is less than 20%, the CO / CO2 equilibrium conversion rate is ≥99% within the operating temperature ≤320℃ and the operating pressure range of 2.5-4.5MPa. Therefore, by adopting an effective temperature control reactor method, the bed outlet temperature is controlled within 320℃, and only a single reactor is needed to achieve efficient CO / CO2 conversion, reducing device investment and operating energy consumption.

[0005] In this regard, the Chinese invention patent "An isothermal reactor for convenient catalyst replacement and its process method" with an application date of 2019-05-28 and publication number of CN110237778A discloses an isothermal reactor for convenient catalyst replacement and its process method, which is characterized in that the reactor adopts a concentric circle design, the catalyst is loaded in an annular screen, the screen is loaded into the concentric circle reactor as a whole, and the catalyst is disassembled as a whole, focusing on the structural characteristics of the reactor; the application date is 2021-06-22, and the publication number is CN The Chinese invention patent No. 113289663A, "Method for preparing a methanation catalyst for an isothermal fixed bed", discloses a method for preparing a methanation catalyst for an isothermal fixed bed, in which a mesoporous carrier is prepared by using silicon nitride and alumina; the Chinese invention patent No. CN204247177U, "An adiabatic-isothermal methanation reactor", with an application date of 2014-11-24 and a publication number of CN204247177U, discloses an adiabatic-isothermal methanation reactor, in which an adiabatic section and an isothermal section are arranged, and the isothermal section is a shell-and-tube structure.

[0006] The starting point of the catalysts developed in the above patents is to improve the activity of the catalyst, but the intrinsic rate of the CO2 methanation reaction is very fast. In the industrial adiabatic fixed bed reactor, a hot spot appears at 1 / 5 to 1 / 8 of the bed position. The catalyst bed temperature decreases behind the hot spot, making it easy for local high-temperature areas to appear in the methanation catalyst bed, and the catalyst is easy to sinter. At the same time, the catalyst reaction performance on the rear side is not reflected.

[0007] In actual operation, if the temperature control in the methanation reactor is not properly controlled, it is also very easy to cause the bed to overheat, burn through the internal components of the reactor, and cause the catalyst to sinter and deactivate at high temperature. Therefore, in order to make the methanation reaction proceed smoothly in the reactor, the generated heat can be effectively removed, and the purpose of controlling the bed temperature uniformly is achieved, it is necessary to study the use and loading method of the methanation catalyst from a kinetic perspective. Summary of the invention

[0008] The first object of the present invention is to provide a methanation catalyst suitable for high-concentration carbon dioxide, to provide a series of carbon dioxide methanation catalysts and their loading methods, which have the characteristics of simple structure, high reaction efficiency, gentle bed temperature rise and low hot spot temperature, thereby avoiding the generation of local high temperature and solving the problems of catalyst sintering deactivation, low hydrothermal stability, short catalyst life and poor device operation safety.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned methanation catalyst suitable for high-concentration carbon dioxide.

[0010] The third object of the present invention is to provide the use of the above-mentioned methanation catalyst suitable for high-concentration carbon dioxide.

[0011] The first technical solution adopted by the present invention is a methanation catalyst suitable for high-concentration carbon dioxide, which includes the following components by mass percentage: a carrier of 12% to 85%, a carrier modifier of 1 to 75wt%, an active component NiO of 10 to 50wt%, and an auxiliary agent of 1 to 5wt%, and the sum of the mass percentages of the above components is 100%.

[0012] The present invention is also characterized in that: The carrier includes Al2O3 and ZrO2, and the mass ratio of Al2O3 to ZrO2 is 0.67-35:1; The carrier modifier is nitrogen-doped mesoporous carbon and silicon carbide. The mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3. The nitrogen content in the nitrogen-doped mesoporous carbon is 1.5-12%, and the specific surface area is 800-1200m 2 / g, average pore size is 4~8.1nm; The additives include CeO2, MnO2 and MgO, the mass ratio of CeO2 to MnO2 is 1~5:1, and the mass ratio of MnO2 to MgO is 1:1~1.05.

[0013] The second technical solution adopted by the present invention is a method for preparing a methanation catalyst suitable for high-concentration carbon dioxide, and the specific steps are as follows: S1, stirring the support modifier at 600 rpm and ultrasonically dispersing it in the salt solution to form a suspension, and heating the suspension to 50-80°C; S2. Dissolve the weighed Al, Zr, Ce, Ni, and Mn salts in deionized water to form a first precursor salt solution, heat the first precursor salt solution and the precipitant solution to 50-80° C., and drop them into the heated suspension to perform the first precipitation, maintain the solution pH at 7-8 and continue stirring to form a mixed solution; S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, add a precipitant, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 1-2 hours to obtain a precipitate; S4. After precipitation, the entire solution is hydrothermally aged at 110-150°C for 2-3 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping, and washing until the conductivity of the filtrate is 50-500 μS / cm, and then dried. After drying, it is calcined at 300-600° C. in a nitrogen atmosphere for 4-12 hours to obtain a methanation catalyst suitable for high-concentration carbon dioxide, which includes the following components by mass percentage: 12%-85% of a carrier, 1%-75% of a carrier modifier, 10%-50% of an active component NiO, and 1%-5% of an auxiliary agent, and the sum of the mass percentages of the above components is 100%.

[0014] The present invention is also characterized in that: The ultrasonic frequency in S1 is 40~80kHZ and the power is 200~800kW; The salt solution is a nitrate solution or a sulfate solution; the mass concentration of the salt solution is 0.5-5%, and the solid-liquid weight ratio of the suspension is 1:20-50.

[0015] The molar ratio of the first precursor salt solution to the precipitant in S2 is 0.1-1.1:1, and the precursor salt solution is composed of nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate, and zirconium nitrate; The precipitant solution is any one of sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate.

[0016] The third technical solution adopted by the present invention is the application of a methanation catalyst suitable for high-concentration carbon dioxide. The method for loading the methanation catalyst includes a catalyst active layer arranged in a reactor and an inert filler layer located at both ends of the catalyst active layer. The catalyst active layer is composed of catalyst A, catalyst B and catalyst C. The catalyst active layer is arranged in three layers in sequence along the direction of air flow. The first layer of catalyst along the direction of air flow is catalyst A and catalyst B, the second layer of catalyst is catalyst A, catalyst B and catalyst C, and the third layer of catalyst is catalyst A and catalyst C.

[0017] The present invention is also characterized in that: Each layer of catalyst A, catalyst B and catalyst C can be divided into several small layers of different thicknesses. The mixing weight ratio of catalyst A and catalyst B in the first catalyst active layer is 3:0~2, and the weight ratio of catalyst B shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst B in the second catalyst active layer is 1~2:3, and the mixing weight ratio of catalyst B and catalyst C is 3:0~1, and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst C in the third catalyst active layer is 3:0~1, and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction.

[0018] In catalyst A, by mass percentage, the content of Al2O3 is 10-30wt%, the content of ZrO2 is 2-5wt%, the content of carrier modifier is 40-75wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the content of active component NiO is 10-15wt%, the content of auxiliary agent is 1-5wt%, the mass ratio of CeO2 to MnO2 is 1-5:1, and the mass ratio of MnO2 to MgO is 1:1-1.05; In catalyst B, by mass percentage, the content of Al2O3 is 20-50wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 15-30wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the content of active component NiO is 20-40wt%, the content of auxiliary agent is 1-5wt%, the mass ratio of CeO2 to MnO2 is 1-5:1, and the mass ratio of MnO2 to MgO is 1:1-1.05; In catalyst C, by mass percentage, the content of Al2O3 is 40~60wt%, the content of ZrO2 is 2~10wt%, the content of carrier modifier is 1~10wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3~3, the content of active component NiO is 25~50wt%, the content of auxiliary agent is 1~5wt%, the mass ratio of CeO2 and MnO2 is 1~5:1, and the mass ratio of MnO2 and MgO is 1:1~1.05.

[0019] The inert filler layer is filled with a cylindrical or Raschig ring type, and the inert filler layer is composed of one or more of ceramic balls, corundum, silicon carbide, boron nitride or magnesium oxide mixed in any ratio; The shapes of catalyst A, catalyst B and catalyst C are cylindrical, spherical, four-hole wheel-shaped or five-hole wheel-shaped. The catalysts in the same catalyst active layer have the same shape, while the catalysts in different catalyst active layers have different shapes.

[0020] The entire reaction process is carried out in a reactor. During the entire reaction process, the process conditions are to control the bed temperature to be 240-290°C, the hot spot temperature to be 330°C-500°C, and the reactor gas outlet temperature to be less than or equal to 300°C.

[0021] The beneficial effects of the present invention are: (1) The preparation method of the carbon dioxide methanation catalyst of the present invention adopts a series of catalysts, the catalysts have good heat resistance and hydrothermal stability, and the performance presents a gradient distribution. The filling method of the present invention can effectively reduce the hot spot temperature of the bed, reduce the concentration gradient of the catalyst axial direction, slow down the intensity of the methanation reaction, achieve gentle temperature rise in the bed, effectively avoid the risk of local high temperature area and catalyst sintering deactivation, and extend the service life of the catalyst and the reactor; (2) The carbon dioxide methanation catalyst of the present invention adopts the filling structure of the present invention, and there is no need to change the reactor structure. When the CO2 content at the reaction gas inlet is within 20%, a single reactor can be used to achieve efficient CO2 conversion, with a small bed temperature rise and high safety. There is no need to introduce circulating gas or steam dilution, which saves energy and reduces consumption, and also effectively reduces equipment investment and operating costs. DETAILED DESCRIPTION

[0022] The present invention is described in detail below in conjunction with specific implementation modes.

[0023] A methanogenic catalyst suitable for high-concentration carbon dioxide includes the following components by weight percentage: a carrier of 12% to 85%, a carrier modifier of 1 to 75wt%, an active component NiO of 10 to 50wt%, an auxiliary agent of 1 to 5wt%, and the sum of the weight percentages of the above components is 100%; Further, the carrier includes Al2O3 and ZrO2, and the mass ratio of Al2O3 to ZrO2 is 0.67-35:1; The carrier modifier is nitrogen-doped mesoporous carbon and silicon carbide, the ratio of the two is 1:0.3~3, the nitrogen content in the nitrogen-doped mesoporous carbon is 1.5~12%, and the specific surface area is 800~1200m 2 / g, average pore size is 4~8.1nm; The additives include CeO2, MnO2 and MgO, the mass ratio of CeO2 to MnO2 is 1~5:1, and the mass ratio of MnO2 to MgO is 1:1~1.05.

[0024] The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide comprises the following specific steps: S1, stirring the support modifier at 600 rpm and ultrasonically dispersing it in the salt solution to form a suspension, and heating the suspension to 50-80°C; Among them, the ultrasonic frequency is 40~80kHZ and the power is 200~800kW; The salt solution is a nitrate solution or a sulfate solution; the mass concentration of the salt solution is 0.5-5%, and the solid-liquid weight ratio of the suspension is 1:20-50.

[0025] S2. Dissolve the weighed Al, Zr, Ce, Ni, and Mn salts in deionized water to form a first precursor salt solution, heat the first precursor salt solution and the precipitant solution to 50-80° C., and drop them into the heated suspension to perform the first precipitation, maintain the solution pH at 7-8 and continue stirring to form a mixed solution; The precursor salt solution is composed of nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate and zirconium nitrate; and the precipitant solution is any one of sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate.

[0026] The molar ratio of the first precursor salt solution to the precipitant is 0.1-1.1:1.

[0027] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, add a precipitant, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 1-2 hours to obtain a precipitate; S4. After precipitation, the entire solution is hydrothermally aged at 110-150°C for 2-3 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping, and washing until the conductivity of the filtrate is 50-500 μS / cm, and then dried. After drying, the precipitate is calcined at 300-600° C. for 4-12 hours in a nitrogen atmosphere to obtain a methanation catalyst suitable for high-concentration carbon dioxide, which comprises the following components by mass percentage: 12%-85% of a carrier, 1%-75% of a carrier modifier, 10%-50% of an active component NiO, and 1%-5% of an auxiliary agent, and the sum of the mass percentages of the above components is 100%; The invention is applicable to the application of a methanation catalyst for high-concentration carbon dioxide. The loading method of the methanation catalyst includes a catalyst active layer arranged in a reactor and an inert filler layer located at both ends of the catalyst active layer. The catalyst active layer is composed of catalyst A, catalyst B and catalyst C. The catalyst active layer is arranged in three layers in sequence along the flow direction of the gas flow. The first layer of catalysts along the flow direction of the gas flow are catalyst A and catalyst B, the second layer of catalysts are catalyst A, catalyst B and catalyst C, and the third layer of catalysts are catalyst A and catalyst C.

[0028] Furthermore, each layer of catalyst A, catalyst B and catalyst C can be divided into several small layers of different thicknesses. The mixing weight ratio of catalyst A and catalyst B in the first catalyst active layer is 3:0-2, and the weight (i.e., thickness) of catalyst B increases layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst B in the second catalyst active layer is 1-2:3, and the mixing weight ratio of catalyst B and catalyst C is 3:0-1, and the weight ratio of catalyst C increases layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst C in the third catalyst active layer is 3:0-1, and the weight ratio of catalyst C increases layer by layer along the airflow direction. The reactor is a shell-and-tube temperature-controlled reactor, the catalyst is loaded in the shell layer, and the water channel supplies and removes heat through the tube layer.

[0029] Among them, in catalyst A, by mass percentage, the content of Al2O3 is 10~30wt%, the content of ZrO2 is 2~5wt%, the content of carrier modifier is 40~75wt%, the mass ratio of nitrogen-doped mesoporous carbon and silicon carbide is 1:0.3~3, the content of active component NiO is 10~15wt%, the content of auxiliary agent is 1~5wt%, the mass ratio of CeO2 to MnO2 is 1~5:1, and the mass ratio of MnO2 and MgO is 1:1~1.05.

[0030] In catalyst B, by mass percentage, the content of Al2O3 is 20~50wt%, the content of ZrO2 is 2~10wt%, the content of carrier modifier is 15~30wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3~3, the content of active component NiO is 20~40wt%, the content of auxiliary agent is 1~5wt%, the mass ratio of CeO2 to MnO2 is 1~5:1, and the mass ratio of MnO2 and MgO is 1:1~1.05.

[0031] In catalyst C, by mass percentage, the content of Al2O3 is 40-60wt%, the content of ZrO2 is 2-10wt%, the content of carrier modifier is 1-10wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the content of active component NiO is 25-50wt%, the content of auxiliary agent is 1-5wt%, and the mass ratio of CeO2 to MnO2 is 1-5:1. The mass ratio of MnO2 and MgO is 1:1~1.05.

[0032] The inert filler layer is filled with a cylindrical or Raschig ring type, and the inert filler layer is composed of one or more of ceramic balls, corundum, silicon carbide, boron nitride or magnesium oxide mixed in any ratio; The shapes of catalyst A, catalyst B and catalyst C are cylindrical, spherical, four-hole wheel-shaped or five-hole wheel-shaped. The catalysts in the same catalyst active layer have the same shape, while the catalysts in different catalyst active layers have different shapes. This allows the catalysts in each bed to be mixed evenly and facilitates segmented loading, thereby achieving the purpose of facilitating industrial loading and use.

[0033] The above entire reaction process is carried out in a reactor. During the entire reaction process, the process conditions are to control the bed temperature to be 240-290°C, the hot spot temperature to be 330°C-500°C, and the reactor gas outlet temperature to be less than or equal to 300°C.

[0034] The principle of the present invention is as follows: Mesoporous carbon has a well-developed mesoporous structure, which is beneficial to the molecular diffusion of reactants and products, and also to the transfer of reaction heat; nitrogen doped in mesoporous carbon is beneficial to promoting electron transfer and improving the reduction ability of the catalyst; nitrogen doping is beneficial to the loading and dispersion of Ni, promotes the reduction of Ni, and is beneficial to improving the low-temperature activity and high-temperature stability of the catalyst.

[0035] The catalyst of the present invention uses ZrO2-Al2O3 and nitrogen-doped mesoporous carbon or SiC as a composite carrier. The addition of ZrO2 improves the electron transfer ability and acidity of the Al2O3 carrier. The surface of the nitrogen-doped material can adsorb a large amount of hydrogen and transfer it to the active site on the catalyst surface to increase the rate of the hydrogenation reaction. MgO modification is beneficial to improving the adsorption activity performance of CO2, which is beneficial to improving the activity of the catalyst in the low-temperature methanation reaction of CO2. It also has the characteristics of excellent thermal conductivity and electron transfer performance, and simultaneously improves the low-temperature activity and high-temperature resistance of the catalyst. The hydrophobicity of the nitrogen-doped mesoporous carbon material is beneficial to the desorption of water generated after the methanation of carbon dioxide, and improves the methanation performance of carbon dioxide at low temperature. The introduction of nitrogen-doped mesoporous carbon and the interaction of Ni active components promote the effective dispersion of the active component Ni of the molded catalyst. The Ni grains after roasting are small, the reaction activation temperature is low, and it has good low-temperature reaction activity. It is particularly suitable for methanation heat transfer reactors and can effectively reduce the investment in reactor equipment and operating costs. At the same time, after the introduction of nitrogen-doped mesoporous carbon into the catalyst, carbon sites are formed on the surface of the catalyst. The mesoporous channels are conducive to heat and mass transfer, and nitrogen doping promotes the mobility of electrons on the surface. The formed carbon sites inhibit the generation and further expansion of carbon deposits, and improve the catalyst's resistance to carbon deposits. The in-situ introduction of SiC into the catalyst further enhances the catalyst's thermal conductivity and hydrothermal stability. After the catalyst precursor is subjected to high-temperature hydrothermal treatment, it is beneficial to enhance the interaction between the active components and the additives and carriers, which is beneficial to improving the high temperature resistance and hydrothermal stability while further improving the catalytic performance. The introduction of Ce and Mn additives further improves the activity and stability of the catalyst.

[0036] Since the methanation reaction rate is fast and the heat release is large, when using the temperature-controlled methanation process, the heat transfer effect is limited by simply using physical methods. Therefore, using a single catalyst system cannot achieve a good temperature control effect. This patent creatively uses the same preparation method to change the active components and carrier composition to prepare a series of catalysts with different effects. Here, three catalysts are creatively mixed to achieve the purpose of reasonably controlling the reaction temperature of the catalyst bed, avoiding the generation of temperature rise or local hot spots, and extending the service life of the catalyst, thereby exerting a synergistic catalytic effect.

[0037] In the present invention, three layers of catalyst active layers are sequentially arranged along the flow direction of the gas flow. In addition to arranging multiple layers of catalyst active layers, the mixing ratio of the two catalysts in each layer is also limited. From a kinetic perspective, it is found that the hot spot temperature of the catalyst is closely related to the intrinsic activity of the catalyst. For this reason, it is considered to increase the amount of catalyst with higher methanation activity and higher hydrothermal stability layer by layer along the gas flow direction, while the amount of catalyst with high thermal conductivity, high hydrothermal stability and suitable methanation activity is gradually reduced. The catalyst with weaker methanation activity and stronger hydrothermal stability can effectively lengthen the distance between the zero-meter temperature and the hot spot temperature, ensuring that the bed temperature rise is relatively gentle, and the reaction occurs step by step, so that the hot spot temperature can appear in the catalyst active layer of the second or third layer, and no obvious displacement occurs, thereby achieving the purpose of lowering the hot spot temperature of the bed. The last layer uses a catalyst with higher methanation activity and lower methanation activity, and progresses layer by layer. While further completing the methanation reaction, the reaction gradient is lengthened at the chemical level, and physical heat transfer means are used to make the bed temperature change smoothly. Example 1 The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide, the steps of preparing catalyst A are as follows: S1, 25g nitrogen-doped mesoporous carbon and 30g SiC were stirred at 600rpm and ultrasonically dispersed in a sodium nitrate solution with a mass concentration of 5% to form a suspension with a solid-liquid weight ratio of 1:20, and the suspension was heated to 50°C; Among them, the size of nitrogen-doped mesoporous carbon is >500 mesh, 1100m 2 / g, average pore size 5.5nm, nitrogen content 5%, including 44.51% pyridinic nitrogen, 26.59% pyrrolic nitrogen, 20.52% graphitic nitrogen, 8.38% oxidized nitrogen; SiC size > 500 mesh; The ultrasonic frequency is 40kHZ and the power is 800kW.

[0038] S2. Dissolve 46.6 g of nickel nitrate, 183.3 g of aluminum nitrate, 12.2 g of zirconium nitrate, 4.1 g of manganese nitrate and 7.6 g of cerium nitrate in 1000 mL of deionized water to prepare a first precursor salt solution, and prepare sodium carbonate as a precipitant solution. The molar ratio of the first precursor salt solution to sodium carbonate is 0.1:1. Heat the first precursor salt solution and the precipitant solution to 80°C, and add them dropwise to the heated suspension for the first precipitation. The dropping speed is selected to be completed within 50 min, the stirring speed is 600 rpm, the solution pH is maintained at 7-8 and stirring is continued to start precipitation to form a mixed solution.

[0039] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, containing 0.5g of magnesium nitrate, add a precipitant, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 1h to obtain a precipitate; S4. After the precipitation is completed, the entire solution is hydrothermally aged at 130°C for 2 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping and washing until the conductivity of the filtrate reaches 50 μS / cm, and then dried. After drying, it is calcined at 300°C for 12 h in a nitrogen atmosphere to obtain a catalyst, wherein nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 12%, 25%, 3.5%, 1%, 3% and 0.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 25% and 30% of the catalyst mass, respectively.

[0040] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 25%, 35%, 5%, 1%, 3% and 1% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively, calculated by the mass of oxides.

[0041] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 35%, 50%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2.5% and 2.5% of the catalyst mass, respectively, calculated by the mass of the oxides.

[0042] The reactor packing structure is as follows: two layers of inert filler layers (M layer and N layer) and three layers of catalyst active layers (first layer, second layer and third layer from top to bottom). The first layer is filled with catalysts A and B, which are in the shape of a four-hole wheel and have an outer diameter of 6 mm; the second layer is filled with catalysts A, B and C, which are in the shape of a cylinder and have an outer diameter of 3 mm; the third layer is filled with catalysts A and C, which are both spherical and have an outer diameter of 4 mm; wherein the mixed weight ratio of A and B in the first catalyst active layer is 3:(0-2), and the weight ratio of catalyst B increases layer by layer along the airflow direction; the mixed weight ratio of A, B and C in the second catalyst active layer is (1-2):3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction; the mixed weight ratio of A and C in the third catalyst active layer is 3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction.

[0043] During the entire reaction process, the process conditions are to control the bed temperature at 270°C, the hot spot temperature at 330°C, and the reactor gas outlet temperature less than or equal to 300°C.

[0044] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 360℃, and the gas temperature after passing through the third bed is 280℃, CO2 conversion rate ≥97.5%, CH4 selectivity ≥99.5%, continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0045] Example 2 The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide, the steps of preparing catalyst A are as follows: S1. 32.5 g of nitrogen-doped mesoporous carbon (specifications and content are the same as in Example 1) and 30 g of SiC (size > 500 mesh) are stirred at 600 rpm and ultrasonically dispersed in a sodium nitrate salt solution with a mass concentration of 0.5% to form a suspension with a solid-liquid weight ratio of 1:30. The suspension is heated to 70°C; the ultrasonic frequency is 80 kHz and the power is 600 kW.

[0046] S2. Dissolve 38.8 g of nickel nitrate, 147.1 g of aluminum nitrate, 10.5 g of zirconium nitrate, 4.1 g of manganese nitrate and 7.6 g of cerium nitrate in 1000 mL of deionized water to prepare a first precursor salt solution, and prepare potassium carbonate as a precipitant solution. The molar ratio of the first precursor salt solution to potassium carbonate is 1:10. Heat the first precursor salt solution and the precipitant solution to 50°C, and add them dropwise to the heated suspension for the first precipitation. Maintain the pH of the solution at 7-8 and continue stirring to start precipitation to form a mixed solution.

[0047] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, containing 0.5g of magnesium nitrate, add a precipitant, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 2h to obtain a precipitate; S4. After the precipitation is completed, the entire solution is hydrothermally aged at 150° C. for 2.5 h, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping and washing until the conductivity of the filtrate reaches 100 μS / cm, and then dried. After drying, it is calcined at 600°C in a nitrogen atmosphere for 4 hours to obtain a catalyst, wherein nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 10%, 20%, 3%, 1%, 3% and 0.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 32.5% and 30% of the catalyst mass, respectively.

[0048] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 25%, 35%, 4.5%, 1.5%, 3% and 1% of the catalyst mass respectively, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively, calculated by the mass of oxides.

[0049] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 36%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2.5% and 2.5% of the catalyst mass, respectively, calculated by the mass of oxides.

[0050] The reactor filling structure is the same as that in Example 1, except that: the first layer is cylindrical, the second layer is spherical, and the third layer is a five-hole wheel shape; wherein the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-1), and shows a trend that the weight ratio of catalyst B increases layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is (1-2):3:(0-0.5), and shows a trend that the weight ratio of catalyst C increases layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-0.8), and shows a trend that the weight ratio of catalyst C increases layer by layer along the airflow direction.

[0051] During the entire reaction process, the process conditions are to control the bed temperature at 270°C, the hot spot temperature at 400°C, and the reactor gas outlet temperature less than or equal to 300°C.

[0052] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 356℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥97.2%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0053] Example 3 The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide, the steps of preparing catalyst A are as follows: S1. 30.5 g of nitrogen-doped mesoporous carbon (specifications and content are the same as in Example 1) and 30 g of SiC (size > 500 mesh) are stirred at 600 rpm and ultrasonically dispersed in a sodium sulfate salt solution with a mass concentration of 3% to form a suspension with a solid-liquid weight ratio of 1:50. The suspension is heated to 80°C; the ultrasonic frequency is 60 kHz and the power is 200 kW.

[0054] S2. Dissolve 46.6 g of nickel nitrate, 147.1 g of aluminum nitrate, 10.5 g of zirconium nitrate, 4.1 g of manganese nitrate and 7.6 g of cerium nitrate in 1000 mL of deionized water to prepare a first precursor salt solution, and prepare sodium bicarbonate as a precipitant solution. The molar ratio of the first precursor salt solution to sodium bicarbonate is 1:5. Heat the first precursor salt solution and the precipitant solution to 70°C, and add them dropwise to the heated suspension for the first precipitation. Maintain the pH of the solution at 7-8 and continue stirring to start precipitation to form a mixed solution.

[0055] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, containing 0.5g of magnesium nitrate, add the precipitant solution, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 1.5h to obtain a precipitate; S4. After the precipitation is completed, the entire solution is hydrothermally aged at 110°C for 3 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping and washing until the conductivity of the filtrate reaches 500 μS / cm, and then dried. After drying, it is calcined at 400°C in a nitrogen atmosphere for 8 h to obtain a catalyst, wherein nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 12%, 20%, 3%, 1%, 3% and 0.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 30.5% and 30% of the catalyst mass, respectively.

[0056] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 22%, 38%, 4.5%, 1.5%, 3% and 1% of the catalyst mass respectively, calculated by the mass of oxides, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively.

[0057] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 36%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2.5% and 2.5% of the catalyst mass, respectively, calculated by the mass of oxides.

[0058] The reactor filling structure is the same as that in Example 1, except that: the first layer is spherical, the second layer is a four-hole wheel shape, and the third layer is cylindrical; wherein the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-1), and the weight ratio of B catalyst increases layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is (1-2):3:(0-0.8), and the weight ratio of C catalyst increases layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-1), and the weight ratio of C catalyst increases layer by layer along the airflow direction.

[0059] During the entire reaction process, the process conditions are to control the bed temperature at 270°C, the hot spot temperature at 500°C, and the reactor gas outlet temperature less than or equal to 300°C.

[0060] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 355℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥97.1%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0061] Example 4 The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide, the steps of preparing catalyst A are as follows: S1. 27.5 g of nitrogen-doped mesoporous carbon (specifications and content are the same as in Example 1) and 30 g of SiC (size > 500 mesh) are stirred at 600 rpm and ultrasonically dispersed in a sodium nitrate salt solution with a mass concentration of 5% to form a suspension with a solid-liquid weight ratio of 1:20. The suspension is heated to 50°C; the ultrasonic frequency is 40 kHz and the power is 800 kW.

[0062] S2. Dissolve 38.8 g of nickel nitrate, 183.9 g of aluminum nitrate, 10.5 g of zirconium nitrate, 4.1 g of manganese nitrate and 7.6 g of cerium nitrate in 1000 mL of deionized water to prepare a first precursor salt solution, and prepare potassium bicarbonate as a precipitant solution. The molar ratio of the first precursor salt solution to potassium bicarbonate is 0.1:1. Heat the first precursor salt solution and the precipitant solution to 80°C, and add them dropwise to the heated suspension for the first precipitation. The dropping speed is selected to be completed within 50 min, the stirring speed is 600 rpm, the pH of the solution is maintained at 7-8, and stirring is continued to start precipitation to form a mixed solution.

[0063] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, containing 0.5g of magnesium nitrate, add the precipitant solution, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 2h to obtain a precipitate; S4. After the precipitation is completed, the entire solution is hydrothermally aged at 130°C for 2 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping and washing until the conductivity of the filtrate reaches 50 μS / cm, and then dried. After drying, it is calcined at 400°C in a nitrogen atmosphere for 8 h to obtain a catalyst, wherein nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 10%, 25%, 3%, 1%, 3% and 0.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 27.5% and 30% of the catalyst mass, respectively.

[0064] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 23%, 37%, 4.5%, 1.5%, 3% and 1% of the catalyst mass respectively, calculated by the mass of oxides, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively.

[0065] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 36%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2.5% and 2.5% of the catalyst mass, respectively, calculated by the mass of oxides.

[0066] The reactor filling structure is the same as that in Example 1, except that: the first layer is spherical, the second layer is cylindrical, and the third layer is a five-hole wheel shape; wherein the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-1), and the weight ratio of B catalyst increases layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is (1-2):3:(0-1), and the weight ratio of C catalyst increases layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-0.5), and the weight ratio of C catalyst increases layer by layer along the airflow direction.

[0067] During the entire reaction process, the process conditions are to control the bed temperature at 270°C, the hot spot temperature at 380°C, and the reactor gas outlet temperature less than or equal to 300°C.

[0068] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 352℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥96.8%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0069] Example 5 The preparation method of the methanation catalyst suitable for high-concentration carbon dioxide, the steps of preparing catalyst A are as follows: S1. 27.5 g of nitrogen-doped mesoporous carbon (specifications and content are the same as in Example 1) and 30 g of SiC (size > 500 mesh) are stirred at 600 rpm and ultrasonically dispersed in a sodium nitrate salt solution with a mass concentration of 5% to form a suspension with a solid-liquid weight ratio of 1:20. The suspension is heated to 50°C; the ultrasonic frequency is 40 kHz and the power is 800 kW.

[0070] S2. Dissolve 42.7 g of nickel nitrate, 183.9 g of aluminum nitrate, 6.9 g of zirconium nitrate, 4.1 g of manganese nitrate, and 7.6 g of cerium nitrate in 1000 mL of deionized water to prepare a first precursor salt solution, and prepare sodium carbonate as a precipitant solution. The molar ratio of the first precursor salt solution to sodium carbonate is 0.1:1. Heat the first precursor salt solution and the precipitant solution to 80°C, and add them dropwise to the heated suspension for the first precipitation. The dropping speed is selected to be completed within 50 min, the stirring speed is 600 rpm, the solution pH is maintained at 7-8, and stirring is continued to start precipitation to form a mixed solution.

[0071] S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, containing 0.5g of magnesium nitrate, add the precipitant solution, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 2h to obtain a precipitate; S4. After the precipitation is completed, the entire solution is hydrothermally aged at 130°C for 2 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping and washing until the conductivity of the filtrate reaches 50 μS / cm, and then dried. After drying, it is calcined at 400°C in a nitrogen atmosphere for 8 h to obtain a catalyst, wherein nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 11%, 25%, 2%, 1%, 3% and 0.5% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 27.5% and 30% of the catalyst mass, respectively.

[0072] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 23%, 37%, 4.5%, 1.5%, 3% and 1% of the catalyst mass respectively, calculated by the mass of oxides, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively.

[0073] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 37%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2% and 2% of the catalyst mass, respectively.

[0074] The reactor filling structure is the same as that in Example 1, except that: the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-1), and the weight ratio of catalyst B increases layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is 1:3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction.

[0075] The above entire reaction process is carried out in a reactor. During the entire reaction process, the process conditions are to control the bed temperature to 270°C, the hot spot temperature to 450°C, and the reactor gas outlet temperature to be less than or equal to 300°C.

[0076] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 350℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥96.7%, CH4 selectivity ≥99.5%, continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0077] Example 6 The preparation method and process of the catalyst are the same as those of Example 5, and the difference from Example 5 is that the amount used is different, as follows: The amount of nitrogen-doped mesoporous carbon was 28 g; The first precursor salt solution is prepared by adding 38.8 g of nickel nitrate, 183.9 g of aluminum nitrate, 6.9 g of zirconium nitrate, 4.1 g of manganese nitrate, and 7.6 g of cerium nitrate; the second precursor salt solution contains 0.9 g of magnesium nitrate in the magnesium nitrate solution.

[0078] Catalyst A was obtained, in which nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide accounted for 10%, 25%, 2%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC accounted for 28% and 30% of the catalyst mass, respectively.

[0079] The preparation method is the same as that of catalyst A, and the dosage is adjusted to prepare catalyst B and catalyst C respectively. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 23%, 37%, 4.5%, 1.5%, 3% and 1% of the catalyst mass respectively, calculated by the mass of oxides, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass respectively.

[0080] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 37%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2% and 2% of the catalyst mass, respectively.

[0081] The reactor filling structure is the same as that in Example 5, except that: the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-2), and the weight ratio of catalyst B shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is 1:3:(0-0.5), and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-0.8), and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction.

[0082] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 358℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥96.8%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0083] Example 7 The preparation method and process of catalyst A are the same as those of Example 6, and the difference from Example 6 is that: the dosage is adjusted to prepare catalyst B and catalyst C respectively, wherein in the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide, and magnesium oxide account for 23%, 37%, 4.5%, 1.5%, 3% and 1% of the catalyst mass, respectively, by oxide mass, and nitrogen-doped mesoporous carbon and SiC account for 10% and 20% of the catalyst mass, respectively.

[0084] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 37%, 49%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 2% and 2% of the catalyst mass, respectively.

[0085] The reactor filling structure is the same as that of Example 6, except that: the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-2), and the weight ratio of catalyst B shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is 1:3:(0-0.8), and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-0.7), and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction.

[0086] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest are N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 359℃, and the gas temperature after passing through the third layer is 280℃, CO2 conversion rate ≥97.0%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0087] Example 8 The preparation method of catalyst A and the prepared catalyst A are the same as those in Example 6. The difference from Example 6 is that the amounts of catalyst B and catalyst C are adjusted. In the prepared catalyst B powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 22%, 38%, 4.5%, 1.5%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 15% and 15% of the catalyst mass, respectively.

[0088] In the prepared catalyst C powder, nickel oxide, aluminum oxide, zirconium oxide, manganese oxide, cerium oxide and magnesium oxide account for 38%, 50%, 5%, 1%, 3% and 1% of the catalyst mass, respectively, and nitrogen-doped mesoporous carbon and SiC account for 1% and 1% of the catalyst mass, respectively.

[0089] The reactor filling structure is the same as that in Example 6, except that: the mixing weight ratio of A and B in the first catalyst active layer is 3:(0-2), and the weight ratio of catalyst B increases layer by layer along the airflow direction; the mixing weight ratio of A, B and C in the second catalyst active layer is 1:3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction; the mixing weight ratio of A and C in the third catalyst active layer is 3:(0-1), and the weight ratio of catalyst C increases layer by layer along the airflow direction.

[0090] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 362℃, and the gas temperature after passing through the third layer is 282℃, CO2 conversion rate ≥96.7%, CH4 selectivity ≥99.5%, and continuous operation for 1000h, the hot spot position has not moved significantly, and the catalyst activity remains unchanged.

[0091] Comparative Example 1 The preparation method of the catalyst and the content of each component are the same as those in Example 1. The difference from Example 1 is the filling method: a filling method of two layers of inert filler layers (M layer and N layer) and one layer of catalyst active layer is adopted, and all are filled with catalyst A. The catalysts used are all spherical in shape.

[0092] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the catalyst layer, the temperature is 285℃, the gas temperature after passing through the bed is 220℃, CO2 conversion rate ≥48.5%, CH4 selectivity ≥95.5%, continuous operation for 1000h, the hot spot position, temperature and catalyst activity remain unchanged.

[0093] Comparative Example 2 The preparation method of the catalyst and the content of each component are the same as those in Example 1. The difference from Example 1 is the filling method: two layers of inert filler layers (M layer and N layer) and one layer of catalyst active layer are used, all of which are filled with catalyst B, and the catalyst shape is cylindrical.

[0094] The reaction pressure is 2.5MPa, the raw gas composition is 15%-CO2, the hydrogen-carbon ratio is 4:1, and the rest are N2 / CH4 and other components. It is preheated to 270℃ and enters the catalyst active layer. The hot spot temperature appears in the front section of the catalyst layer, and the temperature is 425℃. After passing through the bed, the gas temperature is 280℃, the CO2 conversion rate is ≥80.5%, and the CH4 selectivity is ≥98.5%. After continuous operation for 1000h, the hot spot position moves downward, the hot spot temperature remains unchanged, and the CO2 conversion rate and CH4 selectivity remain unchanged.

[0095] Comparative Example 3 The preparation method of the catalyst and the content of each component are the same as those in Example 1. The difference from Example 1 is the filling method: a filling method of two layers of inert filler layers (M layer and N layer) and one layer of catalyst active layer is adopted, and all are filled with catalyst C. The catalysts used are all cylindrical in shape.

[0096] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, hot spot temperature appears in the front section of the catalyst layer, the temperature is 450℃, the gas temperature after passing through the bed is 280℃, CO2 conversion rate ≥97.1%, CH4 selectivity ≥99.6%, continuous operation for 1000h, the hot spot position moves down, the hot spot temperature drops to 441℃, the catalyst activity decreases, CO2 conversion rate ≥96.5%, CH4 selectivity ≥99.5.

[0097] Comparative Example 4 The preparation methods of catalyst A, catalyst B and catalyst C are the same as those of Example 1. The difference from Example 1 is that this example is not subjected to hydrothermal treatment, and the filling method is the same as that of Example 1.

[0098] Catalyst loading performance test: reaction pressure 2.5MPa, feed gas composition is 15% -CO2, hydrogen-carbon ratio is 4:1, the rest is N2 / CH4 and other components, preheated to 270℃ entering the catalyst active layer, the hot spot temperature appears in the middle of the second layer, which is 360℃, and the gas temperature after passing through the third bed is 280℃, CO2 conversion rate ≥97.2%, CH4 selectivity ≥99.5%, continuous operation for 1000h, the hot spot temperature drops to 355℃, the hot spot position moves down, the catalyst activity decreases, CO2 conversion rate ≥96.5%, CH4 selectivity ≥99.5%.

[0099] Catalyst performance test: The catalysts prepared in Examples 1 to 8 and Comparative Example 4 were respectively placed at 500°C for 10 hours for reduction and then subjected to carbon dioxide methanation reaction performance evaluation, wherein the reaction evaluation was set at a reaction temperature of 270°C, a reaction pressure of 2.5 MPa, and a raw gas composition of 20%-CO, 80%-H2. The reaction results are shown in Table 1.

[0100] Table 1 Catalyst evaluation results

[0101] The above results illustrate the evaluation results of the catalyst, indicating that different series of catalysts have different activities. By adjusting the composition of the catalyst active components, additives, carriers, etc., the catalyst activity can be flexibly adjusted. The 1000h evaluation results of the embodiment and the comparative example show that the catalyst bed temperature rise is moderate and controllable by adopting the catalyst combination method of the present invention, which can improve the activity and stability of the overall loaded catalyst. The hydrothermal treatment method improves the stability of the hydrothermal atmosphere while promoting the activity of the catalyst.

Claims

1. A methanogenic catalyst suitable for high-concentration carbon dioxide, characterized in that: The composition includes the following components by weight percentage: 12% to 85% of a carrier, 1% to 75% of a carrier modifier, 10% to 50% of an active component NiO, and 1% to 5% of an auxiliary agent. The sum of the weight percentages of the above components is 100%.

2. The methanation catalyst suitable for high concentration carbon dioxide according to claim 1, characterized in that: The carrier comprises Al2O3 and ZrO2, and the mass ratio of Al2O3 to ZrO2 is 0.67-35:1; The carrier modifier is nitrogen-doped mesoporous carbon and silicon carbide, the mass ratio of the nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the nitrogen content of the nitrogen-doped mesoporous carbon is 1.5-12%, and the specific surface area is 800-1200m 2 / g, average pore size is 4~8.1nm; The auxiliary agent includes CeO2, MnO2 and MgO, the mass ratio of CeO2 to MnO2 is 1-5:1, and the mass ratio of MnO2 to MgO is 1:1-1.

05.

3. A method for preparing a methanation catalyst suitable for high-concentration carbon dioxide, characterized in that: The specific steps are as follows: S1, stirring the support modifier at 600 rpm and ultrasonically dispersing it in the salt solution to form a suspension, and heating the suspension to 50-80°C; S2. Dissolve the weighed Al, Zr, Ce, Ni, and Mn salts in deionized water to form a first precursor salt solution, heat the first precursor salt solution and the precipitant solution to 50-80° C., and drop them into the heated suspension to perform the first precipitation, maintain the solution pH at 7-8 and continue stirring to form a mixed solution; S3, continue to drop the second precursor salt solution magnesium nitrate solution into the mixed solution, add a precipitant, maintain the pH of the mixed solution at 7-8, continue stirring for the second precipitation and maintain for 1-2 hours to obtain a precipitate; S4. After precipitation, the entire solution is hydrothermally aged at 110-150°C for 2-3 hours, and then the precipitate is filtered out; S5. The precipitate after hydrothermal aging is subjected to multiple cycles of filter pressing, pulping, and washing until the conductivity of the filtrate is 50-500 μS / cm, and then dried. After drying, it is calcined at 300-600° C. in a nitrogen atmosphere for 4-12 hours to obtain a methanation catalyst suitable for high-concentration carbon dioxide, which includes the following components by mass percentage: 12%-85% of a carrier, 1%-75% of a carrier modifier, 10%-50% of an active component NiO, and 1%-5% of an auxiliary agent, and the sum of the mass percentages of the above components is 100%.

4. The method for preparing a methanation catalyst suitable for high-concentration carbon dioxide according to claim 3, characterized in that: The ultrasonic frequency in S1 is 40~80kHZ and the power is 200~800kW; The salt solution is a nitrate solution or a sulfate solution; the mass concentration of the salt solution is 0.5-5%, and the solid-liquid weight ratio of the suspension is 1:20-50.

5. The method for preparing a methanation catalyst suitable for high-concentration carbon dioxide according to claim 4, characterized in that: The molar ratio of the first precursor salt solution to the precipitant in S2 is 0.1-1.1:1, and the precursor salt solution is composed of nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate, and zirconium nitrate; The precipitant solution is any one of sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate.

6. The use of the methanation catalyst suitable for high concentration carbon dioxide according to any one of claims 1 to 5, characterized in that: The method for loading the methanation catalyst includes a catalyst active layer arranged in a reactor and an inert filler layer located at both ends of the catalyst active layer, wherein the catalyst active layer is composed of catalyst A, catalyst B and catalyst C, and the catalyst active layer is arranged in three layers in sequence along the direction of airflow, wherein the first layer of catalysts along the direction of airflow is catalyst A and catalyst B, the second layer of catalysts is catalyst A, catalyst B and catalyst C, and the third layer of catalysts is catalyst A and catalyst C.

7. The use of the methanation catalyst suitable for high concentration carbon dioxide according to claim 6, characterized in that: Each layer of the catalyst A, catalyst B and catalyst C can be divided into several small layers with different thicknesses. The mixing weight ratio of catalyst A and catalyst B in the first catalyst active layer is 3:0-2, and the weight ratio of catalyst B shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst B in the second catalyst active layer is 1-2:3, the mixing weight ratio of catalyst B and catalyst C is 3:0-1, and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction; the mixing weight ratio of catalyst A and catalyst C in the third catalyst active layer is 3:0-1, and the weight ratio of catalyst C shows a trend of increasing layer by layer along the airflow direction.

8. The use of the methanation catalyst suitable for high concentration carbon dioxide according to claim 7, characterized in that: In the catalyst A, by mass percentage, the content of Al2O3 is 10-30wt%, the content of ZrO2 is 2-5wt%, the content of the carrier modifier is 40-75wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the content of active component NiO is 10-15wt%, the content of the auxiliary agent is 1-5wt%, the mass ratio of CeO2 to MnO2 is 1-5:1, and the mass ratio of MnO2 to MgO is 1:1-1.05; In the catalyst B, by mass percentage, the content of Al2O3 is 20-50wt%, the content of ZrO2 is 2-10wt%, the content of the carrier modifier is 15-30wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3-3, the content of active component NiO is 20-40wt%, the content of the auxiliary agent is 1-5wt%, the mass ratio of CeO2 to MnO2 is 1-5:1, and the mass ratio of MnO2 to MgO is 1:1-1.05; In the catalyst C, by mass percentage, the content of Al2O3 is 40~60wt%, the content of ZrO2 is 2~10wt%, the content of carrier modifier is 1~10wt%, the mass ratio of nitrogen-doped mesoporous carbon to silicon carbide is 1:0.3~3, the content of active component NiO is 25~50wt%, the content of auxiliary agent is 1~5wt%, the mass ratio of CeO2 and MnO2 is 1~5:1, and the mass ratio of MnO2 and MgO is 1:1~1.

05.

9. The use of the methanation catalyst suitable for high concentration carbon dioxide according to claim 6, characterized in that: The inert filler layer is filled in a cylindrical or Raschig ring shape, and the inert filler layer is composed of one or more of porcelain balls, corundum, silicon carbide, boron nitride or magnesium oxide mixed in any ratio; The catalyst A, catalyst B and catalyst C are cylindrical, spherical, four-hole wheel-shaped or five-hole wheel-shaped. The catalysts in the same catalyst active layer have the same shape, while the catalysts in different catalyst active layers have different shapes.

10. The use of the methanation catalyst suitable for high concentration carbon dioxide according to claim 6, characterized in that: The entire reaction process is carried out in a reactor. During the entire reaction process, the process conditions are to control the bed temperature to be 240-290°C, the hot spot temperature to be 330-500°C, and the reactor gas outlet temperature to be less than or equal to 300°C.

Citation Information

Patent Citations

  • Isothermal reactor with function of conveniently and quickly replacing catalyst, and technological method of isothermal reactor

    CN110237778A

  • Preparation method of isothermal fixed bed methanation catalyst

    CN113289663A

  • Adiabatic-isothermal methanation reactor

    CN204247177U

  • Applications of Ni / SiC catalyst to methane production through syngas conversion

    CN102020525A

  • Method for preparing complete methanation catalyst for hydrothermal chemical process

    CN102029161A